Natural polymer composites for sustainable dust suppression: a soil mineralogy-guided chemical design - Yang, Dianqiu; Wang, Wenhao; Zhu, Chenyu (Frontiers in Chemistry, 2025)
Road construction-related dust pollution significantly endangers both environmental sustainability and public health, in contrast to traditional dust management techniques like water spraying, which are resource-demanding. The development of eco-friendly dust suppressants with tailored mineral-polymer interactions remains a critical challenge in sustainable material chemistry. This research created a novel composite dust suppressant using sodium alginate (SA), carboxymethyl cellulose (CMC-Na), hydroxypropyl trimethylammonium chloride chitosan (HTCC), gelatin (GEL), and glycerol (GLY). Through orthogonal experiments, the ideal composition was identified as SA (34.8%), CMC-Na (8.7%), HTCC (34.8%), GEL (4.3%), and GLY (17.4%). The dust suppressant demonstrated superior film-forming properties and enhanced wettability. During performance tests, the dust suppressant achieved over 99% dust reduction at a wind speed of 15 m/s across five different soil types. Analyses using Grey correlation and Pearson correlation were performed to explore the impact of soil composition. The results revealed that soil components, including Al2O3, CaO, SiO2, TiO2, and MnO, improved water retention, agglomeration rate, and wind erosion resistance. The results underscore the vital importance of soil composition in improving the effectiveness of dust suppression. The new suppressant demonstrated significantly better dust control capabilities. This renders it an exceptionally efficient method for reducing dust contamination in road building. Additionally, it provides a feasible method for safeguarding the environment during construction processes. Through cost analysis, compared with traditional water spraying methods, the overall cost is reduced by about 40%. And with a wide range of raw materials and simple preparation, it can meet the needs of large-scale production. This work elucidates the role of polymer-mineral chemistry in dust suppression, offering a scalable, green alternative that bridges environmental engineering and sustainable material science.